Seasonal and Nutrient Supplement Responses in Rumen Microbiota Structure and Metabolites of Tropical Rangeland Cattle - Gonzalo Martinez-Fernandez; Jinzhen Jiao; Jagadish Padmanabha; Stuart E. Denman; Christopher S. McSweeney (Microorganisms, 2020)
This study aimed to characterize the rumen microbiota structure of cattle grazing in tropical rangelands throughout seasons and their responses in rumen ecology and productivity to a N-based supplement during the dry season. Twenty pregnant heifers grazing during the dry season of northern Australia were allocated to either N-supplemented or un-supplemented diets and monitored through the seasons. Rumen fluid, blood, and feces were analyzed before supplementation (mid-dry season), after two months supplementation (late-dry season), and post supplementation (wet season). Supplementation increased average daily weight gain (ADWG), rumen NH3–N, branched fatty acids, butyrate and acetic:propionic ratio, and decreased plasma δ15N. The supplement promoted bacterial populations involved in hemicellulose and pectin degradation and ammonia assimilation: Bacteroidales BS11, Cyanobacteria, and Prevotella spp. During the dry season, fibrolytic populations were promoted: the bacteria Fibrobacter, Cyanobacteria and Kiritimatiellaeota groups; the fungi Cyllamyces; and the protozoa Ostracodinium. The wet season increased the abundances of rumen protozoa and fungi populations, with increases of bacterial families Lachnospiraceae, Ruminococcaceae, and Muribaculaceae; the protozoa Entodinium and Eudiplodinium; the fungi Pecoramyces; and the archaea Methanosphera. In conclusion, the rumen microbiota of cattle grazing in a tropical grassland is distinctive from published studies that mainly describe ruminants consuming better quality diets.